Sodium alginate-zinc oxide nanocomposite film for antibacterial wound healing applications - Abdul Bakil, Siti Natrah; Kamal, Hazirah; Abdullah, ‪Hasan Zuhudi; Idris, ‪Maizlinda Izwana (AMG Transcend Association, 2020)
This study aims to develop sodium alginate (SA) based ZnO nanoparticles as antibacterial film for wound healing applications. As natural materials, sodium alginate has been widely investigated and used in wound healing. The ZnO nanoparticles were incorporated as antibacterial into sodium alginate with different compositions (2, 4, 6, 8, 10 ml). Solvent casting method was performed to prepare a film. The film was characterized by using Fourier Transform Infrared Spectroscopy (FT-IR), Atomic Force Microscopy (AFM) and Field Emission Scanning Electron Microscopy (FESEM). Effectiveness of antibacterial activity was carried out against Gram-negative (Escherichia coli) and Gram-positive (Staphylococcus aureus) to characterize the sample. The results from microstructure analysis indicated that as ZnO nanoparticle compositions increased, the film surface became rough. It was found that sodium alginate incorporated with ZnO had slightly higher antibacterial activities against S. aureus than E. coli. Thus, sodium alginate (SA)-Zinc oxide (ZnO) nanoparticle has the potential to be used as a wound healing material in biomedical applications.